Peranan Employee Stock Ownership Program Memoderasi Hubungan Intellectual Capital Terhadap Kinerja Perusahaan - Putri Estiningtyas; Yefta Andi Kus Noegroho (Owner : Riset dan Jurnal Akuntansi, 2022)
Company performance is the company's ability to use all funds for operational activities. One of the factors that increase or decrease the company's performance is caused by intellectual capital. Intellectual capital is an asset owned by the company in order to provide a competitive advantage. This study aims to examine and analyze the employee stock ownership program in the relationship between intellectual capital and company performance. This research method uses quantitative descriptive using purposive sampling technique and obtained a sample of 38 with the number of observations of 43 banking companies listed on the IDX in 2017-2019. The data was analyzed using the Partial Least Square approach with the WarpPLS 7.0 test tool. The results show that capital employed has a negative and significant effect on company performance. Human capital and structural capital have a significant positive effect on company performance. Relational capital is stated to have a positive but not significant effect on the company's performance. The implementation of the employee stock ownership program as a moderating variable is used to support employee morale, not being able to influence all components of intellectual capital, but only being able to moderate human capital. The results of this study indicate that human resources are the main component in the development of the banking business, especially the provision of employee stock ownership programs that can improve company performance.